Application of Treatment Technology, Grey Water Waste Management and Rainwater Harvesting in the Environment of RW 11 Bandung City - Ash Siddiq, Raden Herdian Bayu; Suryaman, Nia Nuraeni; Martoni, Martoni (Institut Teknologi Nasional, Bandung, 2024)
This project addresses critical water resource challenges in urban areas, particularly in Bandung City, Indonesia, where increased demand due to a high population exacerbates groundwater depletion and clean water scarcity. The area of focus is RW 11, Kel. Sukaluyu, Cibeunying Kaler District, which suffers notably from droughts and a significant lack of clean water. The proposed solution involves the development of portable, home-scale technology for the treatment and reuse of greywater and rainwater. This innovative approach is designed to decrease reliance on groundwater and provide a reliable water source during dry seasons. Additionally, the project aims to educate the local community in RW 11 about the importance of maintaining the groundwater cycle. The ultimate goal is to alleviate water scarcity in the area, especially during drought periods, thereby contributing to sustainable water resource management in urban contexts.